Piloting a research mentorship programme in a low-resource setting in Zimbabwe - Danai T. Zhou; Celia M.J. Matyanga; Munyaradzi Madhombiro; Vinie Kouamou; Precious K. Hove; Sarudzai Muyambo; Elizabeth Gori; Fortunate Farirai; Betty Mukuwapasi; Taona E. Mudhluli; Getrude D. Gwenzi; Enetia D. Bobo; et al. (Journal of Public Health in Africa)
Background: Women continue to be underrepresented in science, technology, engineering, mathematics and medicine (STEMM), globally including in Africa and, indeed in Zimbabwe. The gender gap, absence of formal research mentorship and the male-dominated academic culture common among low- and middle-income countries makes scientific growth dire for Africa- and Zimbabwe-based female science researchers.